Osmoregulation in Barnacles: An Evolutionary Perspective of Potential Mechanisms and Future Research Directions - Sundell, Kristina; Wrange, Anna-Lisa; Jonsson, Per R.; Blomberg, Anders (Frontiers in Physiology, 2019)
Barnacles form a globally ubiquitous group of sessile crustaceans that are particularly common in the coastal intertidal. Several barnacle species are described as highly euryhaline and a few species even have the ability to colonize estuarine and brackish habitats below 5 PSU. However, the physiological and/or morphological adaptations that allow barnacles to live at low salinities are poorly understood and current knowledge is largely based on classical eco-physiological studies offering limited insight into the molecular mechanisms. This review provides an overview of available knowledge of salinity tolerance in barnacles and what is currently known about their osmoregulatory strategies. To stimulate future studies on barnacle euryhalinity, we briefly review and compare with known mechanisms of osmoregulation in other marine invertebrates with focus on crustaceans. Different mechanisms are described based on the current understanding of molecular biology and integrative physiology of osmoregulation. We focus on ion and water transport across epithelial cell layers including transport mechanisms across cell membranes and paracellular transfer across tight junctions as well as on the use of intra- and extracellular osmolytes. Based on this current knowledge we discuss the osmoregulatory mechanisms possibly present in barnacles. We further discuss evolutionary consequences of barnacle osmoregulation including invasion success in new habitats and life-history evolution. Tolerance to low salinities may play a crucial role in determining future distributions of barnacles since forthcoming climate-change scenarios predict decreased salinity in shallow coastal areas. Finally, we outline future research directions to identify osmoregulatory tissues, characterize physiological and molecular mechanisms, and explore ecological and evolutionary implications of osmoregulation in barnacles.